Apologia Kościoła w dzisiejszej Europie Środkowo-Wschodniej - Rossa, Piotr (Stowarzyszenie Teologów Fundamentalnych w Polsce, 2012)
The starting point of the article is expressed in the statement, that apology of the Church exhibits a close dependence on a local dimension. The three aspects of the Church are set in the background of the thesis: universal, local and of the actually gathering community. The identity of the faith, as well as the one of the Church, demands unceasing apology, clarification and dialog. This apologic dimension characterized the Church also in 20th century, in the mid-eastern part of European Continent, during totalitarian persecutions by Hitler’s Nazism and Stalin’s communism. The Catholic answer has acquired a shape of radical Christian witness. Apologic dimension of the Church was highly participated by the Blessed Pope John Paul II, who by His parentage, life and ecclesiastic experience was deeply bound to this part of Europe. These circumstances found their reflection in teaching of the “Slavic Pope” and his activity on the field of beatifications and canonizations, concerned about continual discovery of European spiritual foundation. This task was taken on by the Pope Benedict XVI and is also an unceasing challenge for every local community of the Church in context of socio-political transformations and emerging European unity within the European Union structures. As we recall the times of crisis – wars, “Solidarity”, “Prague Spring”, fall of the Berlin Wall – in these moments the Church was and is discovered as the medium of hope – says the author. This effects with necessity of quest for roots of Europe – those Christian, as well as those Jewish. Giving the witness to this hope is the constant portraying and imitating of the Gospel of Jesus Christ in lives of the Church members.
Apology of The Church in modern Eastern and Central Europe
Keywords: European Union; Europe (Central, Eastern); Berlin Wall; Prague Spring; Solidarity; apology; World War II; transformation (sociopolitical); Judaism; martyrdom; Kościół; Jan Paweł II; Benedykt XVI; Tertio Millenio Adveniente; świadectwo; nadzieja